2021
DOI: 10.3390/cosmetics8020054
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Catalytic Amounts of Selected Cationic Surfactants in the Design of New Synergistic Preservative Solutions

Abstract: Preservation using combinations of antibacterial molecules has several advantages, such as reducing the level of usage and broadening their antimicrobial spectrum. More specifically, the use of quaternary ammonium surfactants (QAS)—which are profusely used in hair care products and some are known as efficient antimicrobial agents—is limited due to some potential cytotoxicity concerns. This study shows that the concentration of some widely used cosmetic preservatives can be decreased when combined with very sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Furthermore, the strains showing DS to DDAC circulated throughout the tenyear study period since 2011 and were again estimated at 28.0% by random inclusion among all clinical P. aeruginosa strains of our hospital [33] . It was previously described that the DDAC MICs of susceptible strains were between 15 mg/L [34] and 20 mg/L [35] , which is consistent with our results for a major part of our DDAC-susceptible strains (8-32 mg/L). Interestingly, Goodarzi et al [36] showed that out of 92 P. aeruginosa hospital strains isolated between 2019 and 2020 (Hamadan City Hospital, Iran), 32.6% had a DDAC MIC ranging from 64 to 128 mg/L as found in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the strains showing DS to DDAC circulated throughout the tenyear study period since 2011 and were again estimated at 28.0% by random inclusion among all clinical P. aeruginosa strains of our hospital [33] . It was previously described that the DDAC MICs of susceptible strains were between 15 mg/L [34] and 20 mg/L [35] , which is consistent with our results for a major part of our DDAC-susceptible strains (8-32 mg/L). Interestingly, Goodarzi et al [36] showed that out of 92 P. aeruginosa hospital strains isolated between 2019 and 2020 (Hamadan City Hospital, Iran), 32.6% had a DDAC MIC ranging from 64 to 128 mg/L as found in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the wide usage of maltol, a broader investigation of its antimicrobial mode of action is still needed. In the literature, the antimicrobial efficacy of maltol was evaluated in several studies [4,20,21]. According to the most detailed study, which took place in 1984, maltol inhibited only 10 out of 39 organisms at pH 6, and 5 of 39 organisms at pH 8, and was ineffective against fungi at either pH tested [19].…”
Section: Discussionmentioning
confidence: 99%
“…F. Schved et al found that maltol, at 20 mmol/L (equal to 2522 ppm), resulted in 0.6 log reduction in CFU/mL of E. coli. However, when added in a combination with nisin, which caused only 0.6 log reduction on its own, they yielded 5.5 log reduction in CFU/mL [20]. In their study, they postulated that maltol destabilize the outer membrane of the Gram-negative E. coli by chelating the positively charged Mg 2+ and Ca 2+ ions, and as a result, permeabilized the cell membrane to enhance the efficacy of nisin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations